Comparação dos processos de eletrodeposição de íons cobre usando reatores de leito fluidizado e leito de jorro - Martins, Rosimeire (Universidade Federal de São Carlos, 2010)
In this work was studied the process of removal of ions has covered simulated effluent gifts in watery having used electrochemical reactor of fluidized stream bed and of stream bed of I gush out whose porous cathodes were composites for conducting copper particles. Applying an factorial planning Box-Behnken the effect of the electric chain had been studied, electrolyte concentration have supported and expansion of the stream bed for the electrode of fluidized stream bed and the effect of the electric chain, thickness of the reactor, distance of the central canal and the electrolyte concentration has supported for the electrode of stream bed of gushes out on the efficiency of chain (EC), income space-time (YC) and energy consumption (CE) of the process for both the reactors. The results had been analyzed statistical and the effect of each variable on the studied answers was made using reply surfaces. It was verified that for the electrode of fluidized stream bed all the studied variable are influential as much in linear terms, quadratic and interactive. The electrolyte concentration was the variable most significant in all the 0 variable reply, while for ECC and YC, was observed that the expansion did not have a significant effect when was applied a chain of 4,0A, however, case had a great increase of the energy consumption in this. For the current greater the increase of the expansion caused a great increase of the ECC and the YC, which had mainly to the improvement of the mass transport; in the case of the energy consumption, also it had a reduction of its value almost that for the half. The condition of excellent for the process of electroplating in ELF is of bigger electrolyte concentration has supported current greater and bigger expansion. In these conditions a high value of ECC and YC occurs simultaneously, with a low value of CEC still considered. In the case of the ELJ, the independent variable distance of the central canal, did not influence in the behavior of the variable reply, indicating that the tax of solid circulation did not have influence on the process. The thickness of the electrode was very significant, being that an increase of the ECC occurs for lesser thicknesses and current greaters that an increase of the income of the electrochemical reactor in terms of the electroplating promotes. The best conditions of process that simultaneously optimize the ECC, YC and CEC for ELJ, are of current greater, lesser thickness of stream bed and greater electrolyte concentration has supported.
Keywords: Eletrodeposição; Metais; Reatores; Leito de jorro; Leito fluidizado; Tratamento de efluentes; Electrodeposition; Spouted bed; Fluidized bed; Effluent treatment; ENGENHARIAS::ENGENHARIA QUIMICA